Item inventory manager / Mohammad Faiz Mohamad Zamri and Nur Muhammad Salim - Mohamad Zamri, Mohammad Faiz; Nur Muhammad, Salim (2015)
To realize this project, extensive research and study have to be done on matrix keypad, Arduino Uno Microcontroller, LCD display and interface circuit. The purpose of this project is to design an inventory manager, which the code data can be saved in Arduino Uno Microcontroller and monitor using LCD module interface. So, the objective of this project is to develop. and design a circuit which consists of the combination of hardware such as matrix keypad, Arduino Uno Microcontroller and LCD module to produce a system that have input and output signal The first parts of this project are discussion with the supervisor which is held in every week, to create and form works the circuit. Final Year Project 1 are mainly the embodiment of our real project which are only consist of planning and construct the circuit use for Final Year Project 2. The second parts of this project are about teamwork with partner which is really important to ensure the works were done due the date. In progress of this project, the works are given out equally. This project can be commercialized because it is cheap to build, portable, will fasten work and will be more precise